(untitled) (Mustansiria Dental Journal, 2018)
Objective: The aim of this study was to assess the plasma antioxidant status in patients with periodontitis using serum albumin concentration as a criterion index. . Materials and methods: This study was conducted on 20 individuals (10 healthy control and 10 with chronic periodontitis). Serum albumin level was detected by the bromcresol green albumin (BCG) colorimetric method. Results: Patients with periodontitis had a significant decrease in the level of serum albumin than that of the healthy subjects (p<0.05). Conclusion: The result of the present study demonstrated decreased level of serum albumin in patients with periodontitis, which indicates decreased antioxidant activity in patients with periodontitis on comparison with the healthy individuals.